Effects of multiple climate change factors on exoenzyme activities and CO2 efflux in a tropical grassland. (September 2020) - Brito de Oliveira, Tássio; de Lucas, Rosymar Coutinho; Scarcella, Ana Silvia de Almeida; Contato, Alex Graça; Pasin, Thiago Machado; Martinez, Carlos Alberto; Polizeli, Maria de Lourdes Teixeira de Moraes
Abstract: Climate change is expected to affect rainfall dynamics and the global average temperature. Here, we evaluated the effects of those changes, the intense water deficit and warming (+2 °C), on a tropical grassland soil. We tested the correlation between soil extracellular enzyme activities (EEA) and soil respiration (CO2 efflux) and temperature and soil water content (SWC). A climate change simulation was performed in a field experiment using a temperature free-air-controlled enhancement facility. SWC was the main driver of changes in EEA. The most affected enzymes were β-glucosidase, xylanase and phosphatase. As SWC declined, the potential activity of β-glucosidase and xylanase decreased, while the activity of phosphatase and CO2 efflux increased ( P  < 0.01). Thus, intense drought periods are likely to have a greater influence on the rates of decomposition and mineralization in the evaluated soil than is the 2 °C increase in mean temperature. Highlights: The temperature increase of 2 °C had low influence in a tropical grassland soil. The soil was more vulnerable to a drought that decreased moisture by 50%. β-glucosidase, xylanase and acid phosphatase were the most affected enzymes.